GAMBARAN ASUPAN ZAT GIZI MAKRO DAN PROSES ASUHAN GIZI PADA PASIEN JANTUNG KORONER DI RSUD PROF D.R W.Z. YOHANES KUPANG - Meirina Loaloka; Maria Helena Dua Nita; Anita Sembiring; Gabriela Imaculata N Dedo Tena (Poltekkes Kemenkes Kupang, 2022)
The prevalence of 2.4 percent is above the national prevalence which is 1.5 percent. The prevalence of coronary heart disease aged 15 years according to East Nusa Tenggara Province, Riskesdas 2013 in Kupang city, was 0.3%. Total patients from January – 23 May 2022 inpatients at Prof. W.Z. Johanes Hospital Kupang as many as 4 patients suffering from coronary heart disease (CHD). Dr. W. Z. Johanes Kupang. Research Methods The method used is a case study research design using observational case studies. Research Results Based on the results of monitoring the food intake of the 3 respondents for 2 days of recall with hospital food consumption, the results for the first respondent were 61.17% of energy intake in the category deficit, the percent of protein intake is 80.42% in the sufficient category, the percent of fat intake is 34.43% in the deficit category, and the percent of carbohydrate intake is 67.24% in the deficit category. For the second respondent, the percent of energy intake is 64.64% in the deficit category, the percent of protein intake is 82.69% in the sufficient category, the percent of fat intake is 29.0% in the deficit category, and carbohydrate intake is 71.32% in the less category. As for the third respondent, the percent of energy intake is 56.04% in the deficit category, the percent of protein intake is 33.65% in the deficit category, the percent of fat intake is 71.01% in the less category, and the percent of carbohydrate intake is 61.6 in the category deficit.